Philosophy and African development theory and practice (Dakar Codesria, 2011)
Philosophy and African Development: Theory and Practice appraises development in a holistic manner. It goes beyond the usual measurement in terms of economic achievement and widens the scope to include the impact that history of ideas, political theory, sociology, social and political philosophy, and political economy have had on development in Africa. It is a departure from the traditional treatment of development by economists who point towards the so-called time-tested assertions and recommendations for 'sustainable development', but which are yet bring about significant change in the economies of the so-called 'developing' societies. It is on account of the failures of the economic development theory, with its tepid prescriptions for 'sustainable development' and 'poverty reduction' that theories of development have now been expanded from mere economic analysis to include considerations of history, sociology, political economy and anthropology, as could be discovered in this book. Most of the contributions in this book have been prepared by philosophers across Africa and the United States who implicitly practise their discipline as one whose most effective modern function would be to appraise the human experience in all its dimensions from the standpoints of modern social and natural sciences, all disciplinary offspring of philosophy itself. With chapters ranging from issues of modernity and religious interpretations, the human right to development, the idea of 'African time', the primacy of mental decolonisation, and the type of education we are offering in Africa today and as a tool for development, to development planning, science, technology and globalisation, as well as issues of post coloniality among others, the tenor of the contributions is not only proportional, but also engaged in the meta-analysis of the theories on which the concept of development is founded and practised. This book is strongly recommended as a useful text in the hands of scholars, researchers and students of development studies. It approaches the important issue of African development from the broad perspective of the social sciences in general, and buttresses this with the keen analytical approach of its contributors.
Includes bibliographical references (p. [231]-254).
Keywords: Philosophy, African